Surface Characterization of Nanoparticles: critical needs and significant challenges - Baer, D. R. (2011)
There is a growing recognition that nanoparticles and other nanostructured materials are sometimes inadequately characterized and that this may limit or even invalidate some of the conclusions regarding particle properties and behavior. A number of international organizations are working to establish the essential measurement requirements that enable adequate understanding of nanoparticle properties for both technological applications and for environmental health issues. Our research on the interaction of iron metal-core oxide-shell nanoparticles with environmental contaminants and studies of the behaviors of ceria nanoparticles, with a variety of medical, catalysis and energy applications, have highlighted a number of common nanoparticle characterization challenges that have not been fully recognized by parts of the research community. This short review outlines some of these characterization challenges based on our research observations and using other results reported in the literature. Issues highlighted include: 1) the importance of surfaces and surface characterization, 2) nanoparticles are often not created equal – subtle differences in synthesis and processing can have large impacts; 3) nanoparticles frequently change with time having lifetime implications for products and complicating understanding of health and safety impacts; 4) the high sensitivity of nanoparticles to their environment complicates characterization and applications in many ways; 5) nanoparticles are highly unstable and easily altered (damaged) during analysis.